SOME ISSUES OF APPLICATION OF THE METHOD OF RECOGNITION OF RIGHTS IN PROTECTION OF CORPORATE RIGHTS (ON THE EXAMPLE OF A LIMITED LIABILITY COMPANY) - Saidov, MAKSUDBEK (YURIST AXBOROTNOMASI, 2025)
The article analyzes the legal and practical aspects of applying the method of recognition of rights in the process of protecting corporate rights using the example of a limited liability company. The article considers the importance of the method of recognition of rights in resolving corporate disputes, its effectiveness and the mechanism of application. The article considers the practical importance of the method of recognition of rights using examples of corporate disputes between LLC participants, disputes related to shares in the authorized capital, and disagreements in the activities of management bodies. At the same time, based on judicial practice, the necessary conditions for the correct application of the method of recognition of rights, its legal basis and problematic aspects are considered.